RESPON MASYARAKAT TERHADAP PELAKSANAAN PROGRAM CSR (CORPORATE SOCIAL RESPONSIBILITY) PT MULTIMAS NABATI ASAHAN DI DESA LALANG KECAMATAN MEDANG DERAS KABUPATEN BATU BARA - Prie Anugrah Hastomo (Welfare StatE, 2013)
Corporate social responsibility or CSR now is an important thing for a company. The attendance of a company in the middle of the society definitely give an impact for the life of the society. The natural resources exploitation and the broken environtment around the company being a negative impact that can not be avoid. And then the realization of CSR is an obligation for a company. CSR being a compensation from the company to the society around the company as a social responsibility. This research object is knowing the Lalang village society`s respond which divided into perception, attitude, and participation for the PT Multimas Nabati Asahan (MNA) CSR program realization in Lalang village, Medang Deras district, regency of Batu Bara. This research type is a descriptive research with the qualitative approachment. The population in this research is the society who lived in PT MNA CSR program area in Lalang village which divided into ten small villages with 6.950 amount of people and 1.820 family. Sample of the research is 182 respondents which taken from 10% of the family in every small villages. The data collecting method are refference study and field study which divided into observation, questionnaire, and interview. Data which has ben obtained from the field then processed and analyzed with  the single table and explained qualitatively. The result of the research shows that the society of Lalang village have a positive perseption and attitude however they have a negative paticipation for the realization of PT MNA CSR program. The positive perception and attitude indicate that the PT MNA CSR programs have been believed as precised and needed by the society of Lalang village. Whereas the negative participation of the society of Lalang village caused by some people of Lalang village feel that they never get along or get the benefit from the PT MNA CSR programs. Keyword: Respon Masyarakat, CSR